Creating Markets in Albania : Taking Advantage of New Trade and Investment Opportunities for a More Robust Private Sector - Country Private Sector Diagnostic - International Finance Corporation (World Bank, Washington, DC, 2022)
Despite a challenging transition period and a string of adverse shocks, in recent decades Albania has made major strides in raising per capita income and integrating into the world economy. A dynamic private sector has become the engine of Albania’s economic development, and its increasing role continues to offer opportunities for expanding the country’s economic base and promoting faster and more diversified export-oriented growth. Albania is endowed with considerable economic assets, including a strategic geographical position, exceptional natural beauty, and abundant renewable and nonrenewable resources. A politically stable environment, improving governance indicators, and a record of dependable macroeconomic policies have supported the process of European Union (EU) accession, which offers a wide array of opportunities for the development of the Albanian private sector. Because a small domestic labor pool and consumer market limit the potential for economies of scale, sustaining Albania’s economic expansion will require intensifying its integration with the global economy. Despite decades of progress, Albania continues to face serious structural and policy challenges. The country’s economic expansion has not been matched by commensurate improvements in productivity. In this context, the World Bank Group has prepared the following country private sector diagnostic (CPSD) to assist the authorities in their efforts to leverage Albania’s geographic location, natural assets, and improved institutional and policy framework to promote diversification, competitiveness, and robust private-sector-led growth. The analysis highlights the importance of improving the business environment while stepping up investments in technology and innovation. The report explores three critical sectors for accelerating and diversifying growth: agribusiness and food processing, tourism, and automotive manufacturing.